2014
DOI: 10.1172/jci75051
|View full text |Cite
|
Sign up to set email alerts
|

p38 signaling inhibits mTORC1-independent autophagy in senescent human CD8+ T cells

Abstract: T cell senescence is thought to contribute to immune function decline, but the pathways that mediate senescence in these cells are not clear. Here, we evaluated T cell populations from healthy volunteers and determined that human CD8+ effector memory T cells that reexpress the naive T cell marker CD45RA have many characteristics of cellular senescence, including decreased proliferation, defective mitochondrial function, and elevated levels of both ROS and p38 MAPK. Despite their apparent senescent state, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
387
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 298 publications
(419 citation statements)
references
References 58 publications
(66 reference statements)
14
387
1
Order By: Relevance
“…The authors showed that the MiDAS resulted from an NADH‐AMPK‐p53‐dependent pathway that elicited a SASP but lacked IL‐1‐dependent factors. We have previously shown CD8 + EMRA T cells to display mitochondrial dysfunction (Henson et al ., 2014). Therefore, we investigated whether the CD8 + EMRA SASP was also governed by a p53‐AMPK‐dependent pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors showed that the MiDAS resulted from an NADH‐AMPK‐p53‐dependent pathway that elicited a SASP but lacked IL‐1‐dependent factors. We have previously shown CD8 + EMRA T cells to display mitochondrial dysfunction (Henson et al ., 2014). Therefore, we investigated whether the CD8 + EMRA SASP was also governed by a p53‐AMPK‐dependent pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we show here that senescent CD8 + T cells exhibited a SASP which differs to that reported for fibroblasts and B and NK cells, in that it is not defined by the expression of IL‐1β and IL‐6. This may relate to our finding that EMRA T cells are unable to phosphorylate mTOR (Henson et al ., 2014), a key molecule in the stabilization and translation of inflammatory cytokine mRNAs (Kafasla et al ., 2014). However, senescent CD8 + T cells do secrete high levels of IL‐18, a pro‐inflammatory cytokine in the IL‐1 family that induces IFN‐γ production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, elderly individuals harbor a higher proportion of terminally differentiated (CD28 − ) memory CD8 + T‐cells, which exhibit strong effector functions constrained by limited proliferative capabilities in tandem with short telomeres (reviewed in Pawelec et al ., 1999). More recently, Akbar and colleagues have provided new insights into the associated molecular defects (Henson et al ., 2014). However, there is limited information regarding the capacity of old humans to mount primary CD8 + T‐cell responses.…”
Section: Introductionmentioning
confidence: 99%